THE CREATIVITY OF NARINE ABGARYAN THROUGH THE PRISM OF MODERN LITERARY CRITICISM - Murodalieva A. Sh; Ekabsons A. V. (Galaxy International Interdisciplinary Research Journal, 2023)
Narine Abgaryan is a writer who wrote her works in Russian from Armenia, a popular domestic blogger.